CHALLENGES AFFECTING INNOVATION IN THE TECHNOLOGY INCUBATION HUBS IN KENYA - Mutunga, Paul Mbithi; Were, Dr. Susan; Ogada, Dr. Kennedy (European Journal of Business and Strategic Management, 2018)
Purpose: The purpose of this paper is to establish the various challenges that technology incubation hubs face in Kenya. Methodology: In this study descriptive and exploratory research design was used. The population of this study consisted of ten technology incubation hubs that are registered in Kenya. The target populations in terms of respondents were the technology entrepreneurs, investors, managers, and innovation hubs staff from each of the innovation hubs. This study used primary data which was collected through the use of structured questionnaires. Data from the questionnaires was analyzed using Statistical Package for Social Science (SPSS) version 20 to derive descriptive results. Results: A conclusion is made that ICT Infrastructure and ICT skills are a key determinant of the level of innovation in the technology incubation hubs in Kenya. Unique contribution to theory, practice and policy: From the study findings, the government should provide effective and latest ICT infrastructure in all technology incubation hubs in Kenya. The government in collaboration with other ICT stakeholders should continuously improve on the provision of ICT and internet connectivity in all counties around the country in order to create a supportive environment for investment in technology incubation hubs in Kenya. Secondly, the government through collaboration with the ministry of education, technical institutions and universities should continuously offer the latest training on ICT skills in order to provide technology incubation hubs with the required human resource capacity in ICT innovation. Key words: Challenges, affecting, innovation, technology, incubation hubs, Kenya